2010
DOI: 10.1248/bpb.33.1331
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Potential of Pralidoxime in Tibial and Sural Nerve Transection-Induced Neuropathic Pain in Rats

Abstract: The present study was designed to investigate the ameliorative potential of pralidoxime in tibial and sural nerve transection-induced neuropathy in rats. Tibial and sural nerve transection was performed by sectioning tibial and sural nerve portions (2 mm) of the sciatic nerve, and leaving the common peroneal nerve intact. The pinprick, acetone, hot and cold tail immersion tests were performed to assess the degree of motor functions, mechanical hyperalgesia, cold allodynia, heat and cold hyperalgesia respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…These behavioral alterations are constantly present and last over 2–3 weeks, but their time course varying upon the model and species [32]. In the present study Tibial and sural nerve transection-induced alterations in the nociceptive threshold, are consistent with the earlier reports [21,31]. Additionally TST also led to functional deficit in experimental animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These behavioral alterations are constantly present and last over 2–3 weeks, but their time course varying upon the model and species [32]. In the present study Tibial and sural nerve transection-induced alterations in the nociceptive threshold, are consistent with the earlier reports [21,31]. Additionally TST also led to functional deficit in experimental animals.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies demonstrated that various transaction, ligation, and crushing of sciatic nerve and its branches induces an ipsilateral mechanical, cold, heat hyperalgesia and allodynia thereby indicating the induction of peripheral neuropathic pain [3,31]. These behavioral alterations are constantly present and last over 2–3 weeks, but their time course varying upon the model and species [32].…”
Section: Discussionmentioning
confidence: 99%
“…Central sensitization of neurons is a result of the motor as well as sensory fibers thus causes decrease in thermal withdrawal latency and increase in flicking response. Various transection, ligation and crushing of sciatic nerve and its branches induces ipsilateral cold, heat hyperalgesia and allodynia thereby indicating the induction of peripheral neuropathic pain [38,39]. These behavioral alterations are constantly present and last over 2-3 weeks, but their time course varying upon the model and species [40].…”
Section: Discussionmentioning
confidence: 99%
“…The common peroneal nerve was not affected since it was kept intact. In two layers, the layers of muscle and skin were sealed off shown in Figure 4 (Kaur et al, 2010).…”
Section: Transsection Of the Tibial And Sural Nervesmentioning
confidence: 99%